Composite life cycle of tropical mesoscale convective systems from geostationary and low Earth orbit satellite observations: method and sampling considerations - Fiolleau, Thomas; Roca, Rémy (Quarterly journal of the Royal Meteorological Society, 2013)
The ability of the current and upcoming space‐borne microwave observing systems to document precipitation processes during the life cycle of tropical convective systems is investigated with emphasis on sampling considerations. A composite technique is introduced that will serve as a Day 1 algorithm for the Megha‐Tropiques mission. It is exemplified using the Tropical Rainfall Measurement Mission (TRMM) satellite observations from the TRMM Microwave Imager (TMI) instrument and the fleet of operational geostationary infrared images for the boreal summer 2009 over the whole intertropical belt. At the system scale, over both land and oceanic regions, rainfall is overall strong at the beginning (the first third) of the life cycle and then smoothly decreases as the system shrinks and dissipates. Larger rain yields are observed for the land systems (∼6 mm h−1 maximum) compared to the systems over ocean (∼4 mm h−1 maximum). An in‐depth analysis of the sensitivity of the results to various aspects of the sampling is performed using simulated observations. The benefit of using various platforms is discussed, including considerations of constellation configuration. The entire Tropics as well as regional scales are explored, revealing the expected improvements from the inclusion of the Megha‐Tropiques observations. The sampling results are also strongly supportive of the use of multiple‐platform microwave observations from the upcoming Global Precipitation Mission constellation to build a mesoscale convective system precipitation composite life cycle, although the merging of the parameters derived from various resolution radiometers would deserve further investigations. Copyright © 2013 Royal Meteorological Society